Effect of Therapeutic Ultrasound and Deep Friction Massage in De-Quervain’s Tenosynovitis - Maira Syed, M. Aazib Sherazi, Anum Zafar, Saima Shumile, Saania Kanwal Khanzada, Amber Shahzad, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the effectiveness of ultrasound therapy and deep friction massage in relieving symptoms of de-quervain’s tenosynovitis Material and methods: This Study Was Conducted In Physiotherapy Department Of Al-Shafi Medical Rehabilitation Complex. It is a Randomized controlled trial. There were 2 groups consisting of 20 patients each (patients with de-qurvain’s tenosynovitis). The data was collected through the following data collection tools. Hand assessment tool (hat). Visual analogue scale (vas). Results: Mean score of Hand Assessment Tool between both groups was -0.550 Std. 0.152 with a P-value of 0.001. Mean score of Visual Analog Score mean difference between both groups was -0.350 Std. 0.205 with a P-value of 0.097. Practical Implication: Postoperatively, the wrist is splinted in a neutral position until the skin sutures are removed. This will minimize the probability of tendon anterior subluxation Conclusion: Ultrasound therapy is effective in treating de-quervain’s tenosynovitis. Deep friction massage is also effective in treating de-quervain’s tenosynovitis. Keywords: Ultrasound therapy, Deep Friction Massage, de Quervain's tenosynovitis, neutral position, Pakistan